2007
DOI: 10.1016/j.fuel.2006.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Biodiesel and FAME synthesis assisted by microwaves: Homogeneous batch and flow processes

Abstract: Fatty acids methyl esters (FAME) have been prepared under microwave irradiation, using homogeneous catalysis, either in batch or in a flow system. The quality of the biodiesel obtained has been confirmed by GC analysis of the isolated product. While the initial experiments have been performed in a small scale laboratory batch reactor, the best experiment has been straightforward converted into a stop-flow process, by the use of a microwave flow system. Compared with conventional heating methods, the process us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
65
0
7

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 160 publications
(74 citation statements)
references
References 13 publications
2
65
0
7
Order By: Relevance
“…Several examples of microwave irradiated transesterification methods have been reported using adapted domestic ovens to use them as flow systems (Saiffudin et al, 2004) or batch laboratory ovens (Mazzocchia et al, 2004) but only moderate conversions were obtained. A more recent study used homogeneous catalysis, both in a batch and in a flow system (Hernando et al, 2007). Leadbeater and Stencel reported the use of microwave heating as a fast, simple way to prepare biodiesel in a batch mode (Leadbeater and Stencel, 2006).…”
Section: Methodsmentioning
confidence: 99%
“…Several examples of microwave irradiated transesterification methods have been reported using adapted domestic ovens to use them as flow systems (Saiffudin et al, 2004) or batch laboratory ovens (Mazzocchia et al, 2004) but only moderate conversions were obtained. A more recent study used homogeneous catalysis, both in a batch and in a flow system (Hernando et al, 2007). Leadbeater and Stencel reported the use of microwave heating as a fast, simple way to prepare biodiesel in a batch mode (Leadbeater and Stencel, 2006).…”
Section: Methodsmentioning
confidence: 99%
“…Previous results showed that application of radio frequency microwave energy offers a fast, easy route to this valuable biofuel with advantages of enhancing the reaction rate and improving the separation process (Hernando et al, 2007;El Sherbiny et al, 2010). In all these attempts conventional alkali homogenous catalysts were employed.…”
Section: Synergy Between Microwave Irradiation and Heterogeneous Catamentioning
confidence: 99%
“…Reflux systems are at minimal risk of explosion because they are operating at atmospheric pressure and because flammable vapors cannot be released into the microwave cavity. Several examples of microwave irradiated transesterification methods have been reported using adapted domestic ovens to use them as flow systems (Saiffudin et al, 2004) or batch laboratory ovens (Mazzocchia et al, 2004) but only moderate conversions were obtained.. A more recent study used homogeneous catalysis, both in a batch and in a flow system (Hernando et al, 2007). Leadbeater and Stencel reported the use of microwave heating as a fast, simple way to prepare biodiesel in a batch mode (Leadbeater and Stencel, 2006).…”
Section: Microwave-enhanced Transesterificationmentioning
confidence: 99%